Cerebral venous sinus thrombosis: - Yadollahikhales, Golnaz; Borhani-Haghighi, Afshin; safari, anahid; Wasay, Mohammad; C.Edgell, Randall (Galen Medical Journal, 2016)
Cerebral venous thrombosis (CVT) is occlusion of dural sinuses and/or cortical veins due to clot formation. It is a potentiallyÂ  Â life-threatening condition that requires rapid diagnosis and urgent treatment. Cerebral venous thrombosis is Â Â more common inÂ  Â females and young people. Pregnancy, postpartum state, contraceptive pills,Â  infection, malignancy, Â hyper-coagulable state, rheumatological disorders, trauma are among the major etiologies of cerebral venous thrombosis. Headache, focal neurologic deficits and seizure were the most common clinical presentations. Different techniques of unenhanced and contrast enhanced Â Â brainÂ  computerized tomography(CT scan)Â  and ,magnetic resonance imaging(MRI) are the most helpful ancillary investigations for diagnosis of Cerebral venous thrombosis. Specific treatment Â of the underlying cause of cerebral venous thrombosis should be considered as the mainstay of the treatment. Anticoagulation with heparin or low molecular weight heparinoidsÂ  is Â the most accepted treatment. In acute phase, medical Â Â or surgical management to decrease intracranial pressure (ICP) is Â Â also recommended. If the patient’s clinicalÂ Â  condition aggravates despite adequate anticoagulation, thrombolysis Â or mechanical thrombectomy can be an additive option.